Feminism in the Time of Transformation. Piotr Piotrowski, Zofia Kulik and the Development of Feminist Art History in Poland - Jakubowska, Agata (Artium Quaestiones, 2022)
This article is an analysis of one area of Piotr Piotrowski’s (1952–2015) activity in the 1990s – his writings on the art of Zofia Kulik and, more specifically, on its feminist dimension. I argue that although Piotrowski was never interested in women’s art in particular, not only did he practise feminist criticism during this period, but he was also a catalyst for the development of a specific form of feminist reflection that was then new in Polish art history. It focused on power relations and did not accept distancing oneself from social and political problems. I analyse it from the perspective of contemporary revisions of the development of feminist discourse after 1989 in Eastern Europe, which critically examines its embeddedness in Western ideas.